Assessment of genetic diversity in chilli genotypes using multivariate analysis - Bhutia, N.D.; Kumar, P.; Chattopadhyay, A. (Indian Journal of Horticulture, 2022)
Assessment of divergence for a set of characters utilizing different multivariate analyses has been effectively utilized in vegetable crops with diverse breeding system. Therefore, a study was carried out for determination of genetic divergence of 22 chilli genotypes. All the studied genotypes could meaningfully be grouped into six-clusters. Cluster I had the maximum of 14 genotypes, while clusters I and III comprised of two genotypes each, while clusters V and VI had one genotype each. The intra- and inter-cluster distance among 20 genotypes revealed that cluster I showed the maximum intra-cluster value (5.868) indicating that genotypes belonging to this cluster were diverse. Hybridization between genotypes belonging to cluster VI or IV and cluster II can be used to combine higher productivity with early maturity that can fit well in the multiple cropping systems. The top three traits, which contributed most towards the genetic divergence were number of primary branches/ plant (13.44%) followed by days to 50% fruiting (12.20%) and fruit length (12.14%). These traits may be used in selecting the genetically diverse parents for hybridization programme to exploit either maximum heterosis or to execute efficient selection in the segregating generation.